A Textual Approach to Understanding Nusantara Muslims - Fathurahman, Oman (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2013)
The Islamic Manuscripts Unit (ILMU) at Pusat Pengkajian Islam dan Masyarakat (PPIM, Center for the Study of Islam and Society) at Universitas Islam Negeri (UIN, State Islamic University) Syarif Hidayatullah, Jakarta, in co-operation with the Masyarakat Pernaskahan Nusantara (Manassa, Indonesian Association for Nusantara Manuscripts), held a short course program on the methodology of philological research with the topic ‘Accumulating Various Perspectives: A Textual Approach to Understanding Nusantara Muslims’. This program, funded by the Directorate of Islamic Higher Education at the Ministry of Religious Affairs, took place from July–September 2012 at UIN Jakarta.DOI: 10.15408/sdi.v20i1.353